Human Swarming with Artificial Swarm Intelligence using a hybrid approach - Raju, Adhina; Shajan, Shajan PX (International Journal of Computer Sciences and Engineering, 2025)
Swarm Intelligence explores swarms of autonomous robots or simulated agents. Little work, however, has been done on swarms of networked humans. Artificial Swarm Intelligence (ASI) strives to facilitate the emergence of a super-human intellect by connecting groups of human users in closed-loop systems modeled after biological swarms. Early studies have shown that “human swarms” can make more accurate predictions than traditional methods for tapping the wisdom of groups, such as votes and polls. Artificial Swarm Intelligence enables groups to form real-time systems online, connecting as ‘human swarms’ from anywhere in the world. A combination of real-time human input and A.I. algorithms, a Swarm Artificial Swarm Intelligence based system combines the knowledge, wisdom, opinions, and intuitions of live human participants as a unified emergent intelligence that can generate optimized predictions, decisions, insights, and judgments. Simply put, Swarm A.I. technology creates amplified intelligence while keeping humans in the loop